Pseudo social status among Mobile Legends Bang Bang gamers in the M05ENG Community of Bangkalan, Indonesia - Diana Putri; Mohtazul Farid (Digital Theory, Culture & Society, 2026)
This study examines the phenomenon of pseudo social status among players of the online game Mobile Legends Bang Bang within the M05ENG community in Bangkalan, Madura. Social interaction among online gamers extends beyond entertainment, giving rise to social structures and status hierarchies in virtual spaces. Gamers construct their identities and self-images through rank achievements, skin ownership, top-up activities, and social media influence. Employing a qualitative method with Edmund Husserl's phenomenological approach, this study reveals the emergence of pseudo social status in the virtual world. Informants selected through purposive sampling expressed pride in the social status they attained in the virtual environment, despite recognizing its illusory nature. Competition among gamers in the M05ENG community is driven not only by the pursuit of victory but also by the desire to gain social validation and symbolic status. The findings further reveal behavioral differences that reflect variations in gaming skills, playing experience, values, attitudes toward other players, and emotional regulation. In addition, the presence of cosplayers who portray Mobile Legends Bang Bang heroes through costumes, accessories, and character-like behaviors reinforces the perception that in-game characters exist beyond the digital realm, creating a powerful illusion of reality.